(untitled) (Update Dental College Journal, 2021)
The presence of megaloblasts and macrocytes in the bone marrow characterizes megaloblastic anaemia. Megaloblastic anaemia is the result of folate and vitamin B12 deficiency in more than 95% of cases. We hereby report a case of megaloblastic anaemia in a 23-year old female having glossitis and a burning sensation on the tongue. The blood picture showed megaloblastic anaemia and haematological tests confirmed the diagnosis. The patient positively responded to vitamin B12 and folic acid supplementation. The presence of oral signs and symptoms offer the dentist an opportunity to participate in the diagnosis of this condition. Early diagnosis is important to prevent deficiency. This paper explains the oral changes induced by dietary deficiency of cobalamin or folate in a patient with megaloblastic anaemia. Update Dent. Coll. j: 2021; 11 (1): 26-28